Kajian Terhadap Common Errors dalam Penerapan Aturan Subject-Verb Agreement Bahasa Inggris - Rini Ekayati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
English as a foreign language that is widely used in the world provides a challenge to every learner. Grammar rules in English are one of the challenges faced by learners, especially in Subject-verb Agreement rules. This article aims to analyze the types of common errors made by students and determine the types of common errors with the highest percentage of common errors found. With a qualitative and quantitative descriptive design, this study chose students in the English Education Study Program, FKIP UMSU as the research sample. Based on the results of the analysis, it was found that there were three types of common errors found in the use of subject-verb agreement rules in English by students at the English Education Study Program, errors between singular/plural subjects, errors in tense selection, and types of errors in the form 'to' form of verb/split of verb. Furthermore, it can be obtained that the highest percentage of errors obtained is in the type of 'to' form of verb/split of verb in question no. 20 where there were 82 students who answered incorrectly with a percentage of 66.12%.